Pengembangan Kemampuan Menulis Narasi Sederhana Berbantuan Media Kolase Origami Siswa Kelas II SDN 2 Golantepus - Wasis Wijayanto; Mellia Nor Halifah (JPKS (Jurnal Pendidikan dan Kajian Seni), 2026)
The difficulty in developing an original and interesting story idea, as well as the inability of students to compose coherent and continuous sentences at school, are obstacles that must be of special concern and must be followed up appropriately. The purpose of this study is to describe the process of origami collage activities in the development of simple narrative writing skills and analyze the work and writing skills of grade II students of SDN 2 Golantepus after the implementation of the media. A qualitative method through a case study approach is used to describe in depth the application of origami collage as a medium for the development of simple narrative writing. The subjects of the study were 9 students from grade II of SDN 2 Golantepus, consisting of 6 girls and 3 boys. Data collection techniques include observation, interviews, documentation, and analysis of student work. The results of the study explained that learning with origami collage media proved effective in developing the ability to write simple narratives for grade II students of SDN 2 Golantepus. The activity of choosing and arranging images and colors encourages students to connect the visual work with the story ideas they will write, thus helping to direct the imagination and clarify the simple narrative stories that students develop.